The Criminal Liability of Air Flight Accidents - Rahmad Wahid Affandi Harahap (LOCUS MEDIA PUBLISHING, 2022)
Aircraft as a means of air transportation has its own characteristics and advantages compared to land and sea transportation modes. This is related to the speed of movement and reaching large areas in a short time. Safe and secure operation is the most important guarantee in aviation, considering the dangers and accidents that are easily caused by the use of an aircraft. The purpose of this study is to determine and analyze criminal liability in aircraft accidents. The results of the study found that the criminal liability of flight captains in aircraft accidents in terms of Law No.1 of 2009 is Article 411 of Law No.1 of 2009 and Article 438 of Law No.1 of 2009, where the two articles can be the basis for holding the flight captain criminally liable in the event of intentionally flying an aircraft that endangers flight security and safety.